2015
DOI: 10.1371/journal.pone.0115272
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Macrophage Foam Cell Formation by 9-Cis β-Carotene Is Driven by BCMO1 Activity

Abstract: Atherosclerosis is a major cause of morbidity and mortality in developed societies, and begins when activated endothelial cells recruit monocytes and T-cells from the bloodstream into the arterial wall. Macrophages that accumulate cholesterol and other fatty materials are transformed into foam cells. Several epidemiological studies have demonstrated that a diet rich in carotenoids is associated with a reduced risk of heart disease; while previous work in our laboratory has shown that the 9-cis β-carotene rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
(46 reference statements)
0
22
0
Order By: Relevance
“…), are vitamin A precursors, constituting the predominant source of vitamin A in most developing countries (up to 90% ) as well as in Western countries especially with respect to vegetarians. Recently, it has also been suggested that cis ‐carotenoids are even more beneficial for the prevention of atherosclerosis and T2D than their all‐ trans isomers . Finally, it is now acknowledged that lutein and zeaxanthin play a role in vision by improving contrast sensitivity and visual acuity and participate in the prevention of age‐related macular degeneration .…”
Section: Introductionmentioning
confidence: 99%
“…), are vitamin A precursors, constituting the predominant source of vitamin A in most developing countries (up to 90% ) as well as in Western countries especially with respect to vegetarians. Recently, it has also been suggested that cis ‐carotenoids are even more beneficial for the prevention of atherosclerosis and T2D than their all‐ trans isomers . Finally, it is now acknowledged that lutein and zeaxanthin play a role in vision by improving contrast sensitivity and visual acuity and participate in the prevention of age‐related macular degeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it was also reported there that the mRNA for βcarotene-15,15′-monooxygenase (BCMO1), which catalyzes the production of retinoids from β-carotene or β-cryptoxanthin, was not detected in RAW264 cells. In contradiction to that, Zolberg et al reported that BCMO1 protein and its product retinol were detected in RAW264.7 cells after the incubation with 9-cis βcarotene (Zolberg Relevy et al, 2015). Another possibility is that both β-carotene and retinol may, at least in part, have almost the same effect on the enhancement of GSH synthesis in RAW264 cells.…”
Section: Discussionmentioning
confidence: 81%
“…In contradiction to that, Zolberg et al. reported that BCMO1 protein and its product retinol were detected in RAW264.7 cells after the incubation with 9‐cis β‐carotene (Zolberg Relevy et al., ). Another possibility is that both β‐carotene and retinol may, at least in part, have almost the same effect on the enhancement of GSH synthesis in RAW264 cells.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, carotenoids induce increases in intracellular glutathione levels by elevating the activity of glutamate-cysteine ligase, the rate limiting enzyme in GSH synthesis [56]. In addition, preventive effects of β-carotene are associated with the β-carotene cleavage enzyme β-carotene 15,15′-monooxygenase (BCMO1) [57]. In the human macrophage cell line THP-1, β-carotene inhibited 7-ketocholesterol (7KC)-induced apoptosis by reducing expression levels of p53, p21, and Bax and inducing expression of AKT, Bcl-2, and Bcl-xL.…”
Section: Preventive Effects Of Carotenoids On Cardiovascular Disease mentioning
confidence: 99%